Trends of respiratory viruses and factors associated with severe acute respiratory infection in patients presenting at a university hospital: a 6-year retrospective study across the COVID-19 pandemic - De Arcos-Jiménez, Judith Carolina; Martinez-Ayala, Pedro; Quintero-Salgado, Ernestina; Lopez-Romo, Rosendo; Briseno-Ramirez, Jaime (Frontiers in Public Health, 2025)
BackgroundThe COVID-19 pandemic significantly disrupted the epidemiology of respiratory viruses, altering seasonal patterns and reducing circulation. While recovery trends have been observed, factors associated with severe acute respiratory infections (SARIs) during pre- and post-pandemic periods remain underexplored in middle-income countries.ObjectiveThis study aimed to analyze the trends in respiratory virus circulation and identify factors associated with SARI in patients attending a tertiary care university hospital in western Mexico over a six-year period spanning the pre-pandemic, pandemic, and post-pandemic phases.MethodsA retrospective study was conducted using data from 19,088 symptomatic patients tested for respiratory viruses between 2018 and 2024. Viral trends were analyzed through interrupted time series (ITS) modeling, incorporating locally estimated scatterplot smoothing (LOESS) and raw positivity rates. Additionally, ITS analysis was performed to evaluate temporal changes in SARI proportions across different phases of the pandemic. Multivariate logistic regression models were applied to determine independent risk factors for SARI across different time periods.ResultsDuring the pandemic (2020–2021), respiratory virus positivity rates significantly declined, particularly for influenza, which experienced a sharp reduction but rebounded post-2022. Respiratory syncytial virus (RSV) demonstrated a delayed resurgence, whereas other respiratory viruses exhibited heterogeneous rebound patterns. ITS modeling of SARI proportions revealed a significant pre-pandemic increasing trend, followed by a slower rise during the pandemic, and a sharp post-pandemic drop in early 2022, before resuming an upward trajectory. Among older adults (>65 years), a marked increase in SARI was observed at the beginning of the pandemic, while younger groups showed more stable patterns. Logistic regression identified advanced age, male sex, cardiovascular disease, obesity, and immunosuppression as major risk factors for SARI, while vaccination consistently showed a protective effect across all periods and subgroups.ConclusionThe COVID-19 pandemic induced persistent shifts in respiratory virus circulation, disrupting seasonal dynamics and modifying the burden of SARI. The findings underscore the importance of continuous surveillance, targeted vaccination programs, and early diagnostics to mitigate severe outcomes. These results highlight the need for adaptive public health strategies in middle-income countries to address evolving respiratory disease threats.